(untitled) (UNED Research Journal, 2022)
Introduction: In the last decades, the natural dispersal area of P. nitens has been subjected to a change in land use. The agricultural frontier has expanded, at the expense of native forest, with the incorporation of productive systems that use high doses of the herbicide glyphosate. The degree of tolerance of the species to the herbicide and its physiological responses are unknown. Objective: To evaluate the biochemical and physiological responses of Pterogine nitens to simulated glyphosate drift. Methods: Greenhouse trials were conducted with one-year-old plants grown in pots. Glyphosate drift was simulated at doses of 0,65 and 130g a.e. ha-1. We measured concentrations of shikimate, photosynthetic pigments, and mineral composition, 20 days after application. Results: Glyphosate increased concentrations of shikimate and decreased concentrations of photosynthetic pigments. It also reduced concentrations of potassium, magnesium, calcium, zinc, manganese, and iron. Conclusions: Glyphosate alters the photochemical stage of photosynthesis by decreasing the concentration of photosynthetic pigments. It also interferes with macro- and micronutrient homeostasis.